Adverse events in the neonatal intensive care unit identified by triggers - Albanese, Fabiana Bragança; Ventura, Deise de Souza; Perroud, Maurício Wesley; Nogueira de Souza, Rafael; Morau, Mariana Vieira; Visacri, Marília Berlofa; Moriel, Patricia (Frontiers in Pharmacology, 2025)
ObjectiveThe main aim of this study was to identify adverse events (AEs) in neonates admitted to a Neonatal Intensive Care Unit (NICU) using a trigger-based approach.MethodsA retrospective observational study was conducted at Hospital Estadual Sumaré -Dr. Leandro Franceschini, Sumaré, SP, Brazil, over 6 months in 2021. Data from 120 electronic medical records of neonates hospitalized for ≥48 h and prescribed at least one medication were analyzed. Seventeen triggers, such as healthcare-associated infections (HAIs), antimicrobial use, accidental extubation, electrolyte disorders, and others, were employed to identify AEs, including those specific to adverse drug reaction (ADRs). AE severity was assessed using the Neonatal Adverse Event Severity Scale (NAESS) and the World Health Organization (WHO) classification, while ADR causality was evaluated using the WHO criteria and the algorithm proposed by Du et at. Risk factors such as gestational age, birth weight, and length of hospital stay were also analyzed.ResultsA total of 249 triggers identified 168 confirmed AEs, resulting in a Positive Predictive Value (PPV) of 67.5%. At least one AE was observed in 50.0% of neonates and 40.8% experienced ADRs. The most frequent triggers that identified AEs included HAIs and antimicrobial use (30.8/100 records, each), followed by hyperglycemia (22.5/100 records), increased frequency of bowel movements (16.7/100 records), and hyponatremia (10.8/100 records). Severe complications such as necrotizing enterocolitis (2.5/100 records) and accidental extubation (5.0/100 records) were also recorded. Triggers with a PPV of 100% included necrotizing enterocolitis, accidental extubation, hypocalcemia, HAIs, and antimicrobial use. According to the NAESS, most AEs were classified as grade 2 - moderate, (44.0%) or grade 3 – severe (51.2%). Critical events, such as life-threatening conditions (grade 4) and death (grade 5), were less common, totaling 4.8%. Regarding ADRs, the majority were classified as possible or unlikely by both methods. The distribution of AEs varied by neonatal subgroups, with extremely preterm showing higher rates of AEs, including hyponatremia (53.8%) and accidental extubation (66.7%). Among all events, elevated serum creatinine (75.0%), necrotizing enterocolitis (66.7%), and hypercalcemia (100.0%) predominantly occurred in neonates with extremely low birth weight (ELBW). In contrast, neonates with appropriate birth weight experienced fewer AEs and lower AE severity. This association was not assessed for gestational age.ConclusionThe findings suggest that prematurity, low birth weight, and prolonged hospitalization are relevant risk factors for AEs in NICUs. Nonetheless, trigger tools proved effective in identifying severe events and enhancing patient safety in this high-risk setting. Prevention strategies based on these findings can help mitigate risks and optimize neonatal care.